Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find the value of [tex]\( x \)[/tex] for which [tex]\( f(x) = g(x) \)[/tex] is true, let's follow these steps in detail:
1. Define the Functions:
- We are given [tex]\( f(x) = -3x + 4 \)[/tex]
- And [tex]\( g(x) = 2 \)[/tex]
2. Set the Functions Equal:
- Since we want to find the value of [tex]\( x \)[/tex] for which [tex]\( f(x) = g(x) \)[/tex], we set the two expressions equal to each other:
[tex]\[ -3x + 4 = 2 \][/tex]
3. Isolate the Variable [tex]\( x \)[/tex]:
- To solve for [tex]\( x \)[/tex], we first need to isolate [tex]\( x \)[/tex] on one side of the equation. Start by getting all constants on one side:
[tex]\[ -3x + 4 - 4 = 2 - 4 \][/tex]
- Simplify both sides:
[tex]\[ -3x = -2 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
- Now, divide both sides by -3 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-2}{-3} \][/tex]
5. Simplify the Expression:
- Simplifying the fraction, we get:
[tex]\[ x = \frac{2}{3} \][/tex]
Thus, the value of [tex]\( x \)[/tex] for which [tex]\( f(x) = g(x) \)[/tex] is:
[tex]\[ x = 0.6666666666666666 \approx \frac{2}{3} \][/tex]
1. Define the Functions:
- We are given [tex]\( f(x) = -3x + 4 \)[/tex]
- And [tex]\( g(x) = 2 \)[/tex]
2. Set the Functions Equal:
- Since we want to find the value of [tex]\( x \)[/tex] for which [tex]\( f(x) = g(x) \)[/tex], we set the two expressions equal to each other:
[tex]\[ -3x + 4 = 2 \][/tex]
3. Isolate the Variable [tex]\( x \)[/tex]:
- To solve for [tex]\( x \)[/tex], we first need to isolate [tex]\( x \)[/tex] on one side of the equation. Start by getting all constants on one side:
[tex]\[ -3x + 4 - 4 = 2 - 4 \][/tex]
- Simplify both sides:
[tex]\[ -3x = -2 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
- Now, divide both sides by -3 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-2}{-3} \][/tex]
5. Simplify the Expression:
- Simplifying the fraction, we get:
[tex]\[ x = \frac{2}{3} \][/tex]
Thus, the value of [tex]\( x \)[/tex] for which [tex]\( f(x) = g(x) \)[/tex] is:
[tex]\[ x = 0.6666666666666666 \approx \frac{2}{3} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.